Aldura Alyatima fi Bath Manakeb Alsayada Aladhimaa ( Fatema Al Zharaa apace upon her) - اسماء عبد عون (مجلة كلية التربية للبنات, 2019)
This search in the virtues of the daughter of the Prophet Muhammad, to read on their boards want to recount loving and faithful), as stated in the introduction to the author, Abdullah Bin Ibrahim Al-Mirghani (D. 1207 H.) to give reasons in writing the manuscript, which was of an introduction and three chapters and a conclusion was the first in the door thanks to the great lady and on her birthday and her marriage and her death and subsequent events and the third in her them prayers and then the finale which was in love with the Prophet and calling for God to pardon and forgiveness and a good end. I was interested in this manuscript by Mirghani, Hadith and all accounts in reference to the virtues of the great lady to examine a manuscript of أadeeth and Sunnah both named therein, and thereupon adopted the Hadith books, including all valid sources and Al-Mustadrak to the Governor (D. 403 H.),as well as the books and translations in the translation of the men and women who were in the manuscript including layers of Ibn Saad (D. 230H.) and AlTabari (D.310 H.) in history and many other sources was an important achievement search Well, sources and references was very important in translating the authors .